EXCESSIVE SALT INTAKE: PREVALENCE AND ECONOMIC BURDEN IN THE RUSSIAN FEDERATION. (April 2021) - Balanova, Yulia; Shalnova, S; Imaeva, A; Kontsevaya, A; Myrzamatova, A; Mukaneeva, D; Khudyakov, M
Abstract : Objective: WHO recommended average salt intake is 5 g/day. However, in the Russian market basket (the minimum food consumption norms approved by the government) include the salt norm is 10.1 g / day for the working population. Aim. To assess the prevalence of excess salt intake (ESI) and the economic burden (EB) of ESI in the Russian Federation (RF) in 2016: direct costs of the health care system and indirect economic losses due to morbidity and mortality from chronic non-communicable diseases (CNCD) associated with ESI. Design and method: A cross-sectional study Epidemiology of cardiovascular diseases in the RF (ESSE) was carried out in 14 Russian regions (2012–13). Randomly selected aged 25–64 years males (N = 8304), females (N = 13464) were included (response rate>80%). Standard epidemiology methods and criteria were used. The prevalence of ESI was determined using questionnaire. Data sources included federal statistics, regulatory documents. Based on prevalence ESI in the RF and relative risks (RR) derived from meta-analyzes, population attributable risk (PAR) for cardiovascular diseases (CVD), stroke, type 2 diabetes (T2D), stomach cancer (SC) was calculated. Indirect costs (IC) associated with ESI included costs of premature death and disability. The calculations were performed in Microsoft Excel 10.0. Results: The prevalence of ESI was 49.9%, higher among males (54.2% vs 47.1%, p < 0, 001). PAR of ESI was 5% for CVD mortality, 6% for CVD morbidity; stroke: 17%&10% accordingly, 18% for DM2 morbidity, and 7% for SC morbidity. The highest contribution of the ESI to the EB is associated with CVD (122.8 billion rubles), where half(68, 1 billion rubles) is attributable to the EB associated with stroke. In the structure of the EB of each analyzed CNCD, ESI cause from 4.5% (CVD) to 16, 1% (stroke) and 17% (for T2D) of the entire burden. The economic burden to CNCD associated with ESI in the RF in 2016 reached 160.9 billion rubles. Conclusions: ESI was found in half of Russian population aged 25–64. In the burden structure the direct costs were only12%, the economics losses were 88%. Total economic impact due to ESI in the RF was 0.19% of the gross domestic product(2016).